Flower production prospects and sustainability challenges in Ethiopia: A systematic review - Mebrat, Shiferaw; Degwale, Alemu; Mekonen, Temesgen; Mebrat, Amare (Frontiers in Environmental Science, 2022)
The people, planet, and profit sustainability concerns emerged as a novel concept in the ethical business governance system in the floriculture industry. In Ethiopia, however, the sectoral sustainability concern is in its infant stage. Currently, the floriculture industry faced many criticisms because its improper cultivation greatly worsened social well-being and the environment. Therefore, the industry needs to examine the current findings about sustainability and explain the apparent discrepancies. As a result, a systematic review was conducted to analyze the sustainability challenges in the floriculture business and its impact on the environment and society. Relevant studies were collected using the Web of Science, Science Direct, PubMed, and Google Scholar databases. Gray literature search from private and governmental institutions was also conducted. Papers outside the topic’s scope or published articles with a weak methodology setup and numerous editorial issues were eliminated. While documents with high relevance to the topic of interest were used as inclusion criteria. Accordingly, 80 articles through databases and 29 papers via gray literature search were collected and chosen for synthesis. In this article, therefore, the Ethiopian floriculture industry sustainability challenges were analyzed along with various empirical findings. The effects of unsustainable flower farming on society, soil and water health were also enclosed. The underlying factors that led to sectoral sustainability problems were addressed and used as debating points for discussion. The paper also contributes to the scientific discussion by highlighting the areas that need further study and the policy ramifications of sustainability in the flower business.